2018
DOI: 10.17691/stm2018.10.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Transparent PEG-Fibrin Gel as a Flexible Tool for Cell Encapsulation

Abstract: The aim of this study was to modify the chemical structure and to optimize the composition of the fibrin gel for effective cell encapsulation. Materials and Methods. We prepared PEGylated fibrin gels using different fibrinogen concentrations (25-50 mg/ml) and PEGfibrinogen molar ratio 10:1 and 5:1 and characterized them via Fourier transform infrared spectroscopy and differential scanning calorimetry. Within the gels, we encapsulated primary culture of fibroblasts and analyzed using light and laser confocal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…10 Natural brin rapidly degrades and is not transparent, so several modications have been suggested to overcome these limitations and, moreover, those have been shown to increase its angiogenic potential. [11][12][13] Among them, PEGylation (modication with functionalized polyethylene glycol (PEG)) is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Natural brin rapidly degrades and is not transparent, so several modications have been suggested to overcome these limitations and, moreover, those have been shown to increase its angiogenic potential. [11][12][13] Among them, PEGylation (modication with functionalized polyethylene glycol (PEG)) is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the aforementioned problems, another common type of brin PEGylation using NHS-functionalized PEG was studied by several groups. 12,15,[18][19][20][21] This type of modication proceeding through the covalent binding of amino groups does not require protein refolding and is easy to carry out. However, despite the good results in biological experiments, no study was dedicated to the structural properties of this modication, though this knowledge could help in understanding cell-matrix interactions and possible ways to tune them.…”
Section: Introductionmentioning
confidence: 99%
“…7,55 The data obtained on the gel structure agreed with the earlier obtained results. 5,73 A positive correlation between fibrin gel stiffness and fibrinogen concentration was shown in previous studies that allows the preparation of fibrin gels with desired mechanical properties in a range of low Young's modulus values (<10 kPa). 74 The PEGylation is another factor, which affects gel stiffness by reducing it.…”
Section: Discussionmentioning
confidence: 78%
“…act as a base of these structures, for example, decellularized tissues [1][2][3] or hydrogels. [4][5][6] Such systems can maintain cell viability, proliferative and physiological activity, and in some cases, initiate and direct cell differentiation. 7,8 At the same time, one of the key challenges of tissue engineering is the preservation of viable cells in these constructs and transplantation of large grafts to replace extensive defects.…”
mentioning
confidence: 99%
“…Its fibrillar structure serves as a scaffold for invading cells which bind to its fibers through cellular receptors and form capillaries. It was showed that the fiber network morphology can be significantly influenced by fibrinogen and thrombin concentrations[ 65 - 67 ], pH[ 68 ], buffers[ 5 ], incorporation of extra molecules[ 27 ], etc.…”
Section: Biological Properties and Their Tuningmentioning
confidence: 99%